2014
DOI: 10.1055/s-0034-1368091
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Gemcitabine for Metastatic Adenocarcinoma during Pregnancy: A Case Report and Review of the Literature

Abstract: We present the case of a 38-year-old woman diagnosed with metastatic adenocarcinoma of the biliary tract in the 18th week of pregnancy. Chemotherapy based on cisplatin and gemcitabine was administered, reaching disease stabilization until late-preterm delivery at 35 + 0 weeks of gestation. The infant was healthy and showed no malformations. Her head circumference was small, yet no neurological and behavioral defects have been detected. Development was normal during 14 months of follow-up. We discuss the implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The standard treatment for unresectable disease is fluoropyrimidine-based or gemcitabine-based chemotherapy. Wiesweg et al reported the use of gemcitabine and cisplatin in the 18th week of pregnancy in a 38-year-old woman diagnosed with metastatic adenocarcinoma of the biliary tract [ 18 ]. Those with locally advanced GBC may respond to newer adjuvant combination chemotherapy and molecular targeted therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment for unresectable disease is fluoropyrimidine-based or gemcitabine-based chemotherapy. Wiesweg et al reported the use of gemcitabine and cisplatin in the 18th week of pregnancy in a 38-year-old woman diagnosed with metastatic adenocarcinoma of the biliary tract [ 18 ]. Those with locally advanced GBC may respond to newer adjuvant combination chemotherapy and molecular targeted therapeutic options.…”
Section: Discussionmentioning
confidence: 99%
“…Liver diseases complicate the courses of about 3% of all pregnancies and may have detrimental effects on the mother and fetus, but CCA during pregnancy is rare. In PubMed database, 14 such cases have been identified during 1975 to 2019 [6][7][8][9][10][11][12][13][14][15][16][17][18][19] . Patients were aged 25 to 40 years, and no risk factor was identified in most patients.…”
Section: Discussionmentioning
confidence: 99%